1005 HEALTH-RELATED QUALITY OF LIFE AND FUTURE RISK OF HEALTH OUTCOMES AMONG OLDER ADULTS LIVING IN AUSTRALIA AND THE UNITED STATES. (14th June 2022) - Phyo, A Z Z; Ryan, J; Gonzalez-Chica, D; Stocks, N; Woods, R; Murray, A; Reid, C; Nelson, M; Tonkin, A; Storey, E; Gasevic, D; Orchard,; et al.
Abstract: Introduction: Poor health-related quality of life (HRQoL) is associated with higher morbidity and mortality in patient populations. However, whether HRQoL is associated with health outcomes among community-dwelling older people requires further investigation. This study aimed to examine whether HRQoL predicts cognitive decline, dementia, cardiovascular disease (CVD), and mortality in community-dwelling older people living in Australia and the United States. Method: A cohort of 19, 106 individuals from the ASPirin in Reducing Events in the Elderly (ASPREE) study, aged 65–98 years, initially free of dementia or CVD, and who completed the HRQoL 12-item short form (SF-12, version-2) at baseline (2010–2014), were followed until June 2017. The physical (PCS) and mental component scores (MCS) of SF-12 were generated using standardized norm-based method. Results: Over a median of 4.7 years, there were 2, 412 cognitive declines, 574 dementia, 922 incident CVD events, and 1, 052 deaths. Using Cox proportional-hazard regression adjusted for a range of covariates, every 10-unit increase in PCS was associated with a 6% lower risk of cognitive decline, a 14% lower risk of incident CVD, and 17% lower risk of all-cause mortality, but was not associated with incident dementia. In contrast, higher MCS was only associated with a 12% and 15% lower risk of cognitive decline and dementia, respectively. Findings did not differ by sex. Conclusion: Our study provides some of the first evidence that HRQoL can be used in combination with clinical data to identify the future risks of health outcomes among older individuals living in the community. Our findings support the decision of the Australian Commission on Safety and Quality in Health Care to incorporate the SF-12 into the annual Patient-Reported Outcome Measures (PROMs assessment.